Clinical outcomes of intracranial nonvestibular schwannomas treated with linac-based stereotactic radiosurgery and radiotherapy - Putipun Puataweepong (2018)
Background: Intracranial nonvestibular schwannomas arising from various cranial nerves excluding CN VIII are uncommon. Recently, stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (SRT) have been widely reported as effective treatment modalities for nonvestibular schwannomas. The purpose of this study was to study the long term clinical outcome for nonvestibular schwannomas treated with both X-Knife and CyberKnife (CK) radiosurgery at one institution. Materials and Methods: From 2004 to 2013, fifty-two nonvestibular schwannoma patients were included in this study, 33 patients (63%) were treated with CK, and 19 (37%) were treated with X-Knife. The majority of the tumors were jugular foramen schwannomas (38%) and trigeminal schwannomas (27%). HSRT was given for 45 patients (86%), whereas CSRT was for 6 (12%) and SRS for 1 (2%). Results: The median pretreatment volume was 9.4 cm3 (range, 0.57-52 cm3). With the median follow up time of 36 months (range, 3-135), the 3 and 5 year progression free survival was 94 % and 88%, respectively. Tumor size was decreased in 13 (25%), stable in 29 (56%), and increased in 10 (19%). Among the latter, 3 (30%) required additional treatment because of neurologic deterioration. No patient was found to develop any new cranial nerve deficit after SRS/SRT. Conclusions: These data confirmed that SRS/ SRT provide high tumor control rates with low complications. Large volume tumors and cystic expansion after radiation should be carefully followed up with neurological examination and MRI, because it may frequently cause neurological deterioration requiring further surgery.